Urethral adenocarcinoma with bilateral iliac and inguinal lymph nodes which revelead by urethra ectropion in a 67-year-old woman: A case report - SOUMANOU, Fouad Kolawale Yde; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; GANDAHO, Isidore Kokou; Djengue, Euodias (My University, 2018)
We reported a case of urethral adenocarcinoma in a 67-year-old woman who was admitted for difficulty voiding, irritative voiding symptoms, bloody urethral discharge and urinary incontinence. Physical examination was realised by gyneacologist and conclued to urological pathology. Urological examination was showed urethral ectropion which was bleeding. She had no fewer, no pelvic pain even less loss weight. Her general state was satisfactory. The lymph nodes of right side inguinal were felt. Computed imaging was showed involvement of right side bladder and bilateral iliac inguinal lymph nodes. Urethral ectropion biopsy anatomopathological screening was conclued to clear cell adenocarcinoma but CIS lesions were not found. The tumor staging was T3N2M0. A radiotherapy was perfomed. The patient was improvement of voiding symptoms and decrease lymph nodes size. Primary urethral carcinomas are rare pathology especially in the woman. Several histological types exist. However, chemotherapy and radiotherapy are very effective on very advanced stages. This cancer may be revealed by an urethral ectropion in a year-old woman.
Keywords: Ectropion; Urethra; Adenocarcinoma; Radiotherapy